2016
DOI: 10.1186/s12884-016-1117-3
|View full text |Cite
|
Sign up to set email alerts
|

Long-term adherence and effects on grip strength and upper leg performance of prescribed supplemental vitamin D in pregnant and recently pregnant women of Somali and Swedish birth with 25-hydroxyvitamin D deficiency: a before-and-after treatment study

Abstract: BackgroundMuscular weakness and severe vitamin D deficiency is prevalent in Somali (veiled) pregnant women, Sweden. The study aims here were to explore adherence to prescribed supplemental vitamin D in new mothers with vitamin D deficiency and its effects on grip strength and upper leg performance in Somali (target group TG) and Swedish women (reference group RG) from spring through winter.MethodsA before- and after study was designed. A cross-sectional sample of women in antenatal care with serum 25-OHD ≤50 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 35 publications
(44 reference statements)
1
10
0
Order By: Relevance
“…The women described increased physical strength during vitamin D treatment, which enabled them to be more active and get more exercise. The results from our qualitative study capture nuances that complements the findings of increased muscle strength in the previous quantitative study (Englund et al, 2017) as well as in other studies (Erkal et al, 2006;Kalliokoski et al, 2013Kalliokoski et al, , 2016Stockton et al, 2011). In our study, the relieved pain enabled increased levels of activity, which could also lead to further experiences of tiredness which were, however, not paralyzing, and thus differed from the tiredness they felt from LLVD.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…The women described increased physical strength during vitamin D treatment, which enabled them to be more active and get more exercise. The results from our qualitative study capture nuances that complements the findings of increased muscle strength in the previous quantitative study (Englund et al, 2017) as well as in other studies (Erkal et al, 2006;Kalliokoski et al, 2013Kalliokoski et al, , 2016Stockton et al, 2011). In our study, the relieved pain enabled increased levels of activity, which could also lead to further experiences of tiredness which were, however, not paralyzing, and thus differed from the tiredness they felt from LLVD.…”
Section: Resultssupporting
confidence: 81%
“…Results showed that the women experienced crippling ill-health with pain, weakness, tiredness, and sleep deprivation, during a period of low levels of vitamin D. They told of how they had not previously received vitamin D for vitamin D deficiency, but as first or second-generation non-western immigrant women, they may have had LLVD for several years before treatment (Bergström et al, 2014;Erkal et al, 2006;Kalliokoski et al, 2013Kalliokoski et al, , 2016.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesize that the increase of uterine size could influence the performance of the tests being the women heavier at the 34 th week of pregnancy, and therefore more uncomfortable during the tests [53]. In this regard, other studies using the squat test (similar to the chair stand test) already found a reduction in the ability to perform the test in later stages of pregnancy [54,55]. Regarding the values for CRF, some hypotheses that could explain the low values obtained in the present study sample are: i) the use of submaximal tests, that estimate the effort based on the heart rate; and ii) the usual false belief that women should not exercise when they are pregnant, that seems to be more evident at late gestation, this may limit women to try harder in the tests [56] iii) later in pregnancy women already have an increased resting heart rate, which can influence results [2,57], iv) due to the increased weight, women are also moving at a higher energy cost later in pregnancy relative to a similar treadmill earlier in pregnancy; they will have a higher rate of perceived exertion later in pregnancy and, thus, want to stop the treadmill test earlier when they are further along in pregnancy [58].…”
Section: Association Of Maternal Physical-fitness Measures With Umbilmentioning
confidence: 93%
“…Regarding aim 1, 99 tests (including 75 different protocols) were used to assess CRF,8 12 13 18 27–108 28 (including 16 different protocols) to assess muscular fitness,8 12 13 61 86 109–122 14 (including 13 different protocols) to assess flexibility,12 13 110 114 123–127 45 tests (including 40 different protocols) to assess balance,110 116 128–167 2 tests using the same protocol to assess speed168 169 and 3 tests using the same protocol were multidimensional 168–170. No results were found for other PF components such as agility or coordination.…”
Section: Resultsmentioning
confidence: 99%